Novel oxazolo[4,5-g]quinazolin-2(1H)-ones: Dual inhibitors of EGFR and Src protein tyrosine kinases - Lin, Jinsheng; Shen, Wei; Xue, Jingwei; Sun, Juan; Zhang, Xue; Zhang, Can (European journal of medicinal chemistry, 2012)
Quinazoline-containing derivatives are an important class of synthetic products and represent an attractive scaffold for EGFR inhibitors. A series of oxazolo[4,5-g]quinazolin-2(1H)-one derivatives were synthesized and the EGFR and Src inhibition activities were evaluated using Gefitinib as lead compound. The three most potent compounds 5y, 5l and 5a each inhibited EGFR at the IC50 value of 61 nM, 67 nM and 78 nM. Among them, 5c also demonstrated excellent inhibition activity against Src with the IC50 value of 3.1 μM. Several of these derivatives also showed good anti-proliferation effects against KB and A498 cells. Compounds 5y showed more potent inhibition activity against EGFR and anti-proliferation activity against KB and A498 cell lines than Gefitinib. [Display omitted] ► New oxazolo[4,5-g]quinazolin-2(1H)-one structure derivatives were synthesized. ► Two compounds showed more potent inhibition activities against EGFR than Gefitinib. ► 5y was more effective in the inhibition of KB and A498 cell lines than Gefitinib.